(untitled) (PerCursos, 2024)
The article deals with Antonio Gramsci’s political pedagogical perspective. Focusing especially on his production carried out in prison, establishing relationships with previous writings, letters from prison in dialogue with important commentators of the author, it will address the concept of human being, work as an educational principle, considerations regarding school organization, the proposal for unique school, highlighting the indispensable teaching role in the teaching and learning process, in line with the fundamental premise of conscious direction to establish a collective will capable of building emancipatory social transformation. In this way, it demarcates the inescapable role of education as a political action strategy capable of becoming revolutionary.